Ion implantation of organic thin films and electronic devices - Scidà, Alessandra <1985> (Alma Mater Studiorum - Università di Bologna, 2013)
Organic semiconductors have great promise in the field of electronics due to their low cost in term of fabrication on large areas and their versatility to new devices, for these reasons they are becoming a great chance in the actual technologic scenery. Some of the most important open issues related to these materials are the effects of surfaces and interfaces between semiconductor and metals, the changes caused by different deposition methods and temperature, the difficulty related to the charge transport modeling and finally a fast aging with time, bias, air and light, that can change the properties very easily. In order to find out some important features of organic semiconductors I fabricated Organic Field Effect Transistors (OFETs), using them as characterization tools. The focus of my research is to investigate the effects of ion implantation on organic semiconductors and on OFETs. Ion implantation is a technique widely used on inorganic semiconductors to modify their electrical properties through the controlled introduction of foreign atomic species in the semiconductor matrix. I pointed my attention on three major novel and interesting effects, that I observed for the first time following ion implantation of OFETs: 1) modification of the electrical conductivity; 2) introduction of stable charged species, electrically active with organic thin films; 3) stabilization of transport parameters (mobility and threshold voltage). I examined 3 different semiconductors: Pentacene, a small molecule constituted by 5 aromatic rings, Pentacene-TIPS, a more complex by-product of the first one, and finally an organic material called Pedot PSS, that belongs to the branch of the conductive polymers. My research started with the analysis of ion implantation of Pentacene films and Pentacene OFETs. Then, I studied totally inkjet printed OFETs made of Pentacene-TIPS or PEDOT-PSS, and the research will continue with the ion implantation on these promising organic devices.